1997
DOI: 10.1002/(sici)1097-0142(19970315)79:6<1069::aid-cncr3>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of lymph node micrometastases from gastric carcinomas

Abstract: The findings of this study indicate that the presence of micrometastases in lymph nodes is an indispensable factor in determining the prognosis of gastric carcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
2
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 16 publications
4
101
2
2
Order By: Relevance
“…In the present study, only a single cancer cell or scattered cancer cells in the lymph nodes were detected in 65% of the 43 patients with CK-positive lymph nodes. It is still unclear whether these single or scattered cancer cells remain alive in the lymph node, or if they are destroyed or removed by the immune response of the host [12]. It was interesting to note, however, that 73% of these patients with only single or scattered cancer cells in the lymph node showed a marked loss of expression of Ecad in their primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, only a single cancer cell or scattered cancer cells in the lymph nodes were detected in 65% of the 43 patients with CK-positive lymph nodes. It is still unclear whether these single or scattered cancer cells remain alive in the lymph node, or if they are destroyed or removed by the immune response of the host [12]. It was interesting to note, however, that 73% of these patients with only single or scattered cancer cells in the lymph node showed a marked loss of expression of Ecad in their primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, micrometastasis in the lymph node has been detected by cytokeratin (CK) immunostaining [12][13][14]. The clinicopathological significance of these so-called micrometastases in the lymph nodes and the correlation of these micrometastases with the reduced expression of E-cadherin (E-cad), which has been recognized as an important factor in tumor metastasis [15], have not been extensively discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Serial sectioning (Isozaki et al, 1997), immunohistochemical staining (Ishida et al, 1997) and more recently reverse transciptase-polymerase chain reaction (RT-PCR) (Mori et al, 1995) will increase the detection of occult metastases.…”
Section: Discussionmentioning
confidence: 99%
“…However, a disadvantage of this approach is that imaging cannot accurately diagnose lymph node micrometastasis. The clinical significance of lymph node micrometastasis in gastric cancers remains controversial (Ishida et al, 1997). Therefore, lymphatic invasion in resected specimens should be examined not only by staining with HE but also with D2-40 to predict lymph node micrometastasis.…”
Section: Lymphatic Invasion and Micrometastasis In Gastric Cancer T Amentioning
confidence: 99%
“…Therefore, radical lymphadenectomy for gastric cancer has become a standard procedure, resulting in the long-term survival of patients with lymph node metastasis (Maehara et al, 1992). Nevertheless, several authors have reported that complete resection with radical lymphadenectomy that led to a nodenegative (pN0) final diagnosis according to routine histological haematoxylin -eosin (HE) staining did not prevent recurrence (Maehara et al, 1996;Siewert et al, 1996;Ishida et al, 1997). The key causative factor of recurrent gastric cancer is lymph node micrometastasis.…”
mentioning
confidence: 99%